C-terminal S-acylation governs membrane distribution, interaction dynamics and function of a plant Rho GTPase - Amir Akerman; Orit Gutman; Keren E. Shapira; Efraim Lewinsohn; Yoav I. Henis; Shaul Yalovsky (PLoS ONE, 2026)
Rho of Plants (ROPs) are plant-specific Rho GTPases that regulate diverse cellular processes. Based on their C-terminal motifs, ROPs are classified as type I or type II. Type-II ROPs lack the canonical CaaL prenylation motif and can be palmitoylated in vitro , yet in vivo evidence for their S-acylation and functional significance has been limited. Here, we investigated the membrane association, lipid modifications and function of the Arabidopsis type-II ROP, ROP10. Confocal microscopy, biochemical fractionation and fluorescence recovery after photobleaching (FRAP) analyses showed that wild-type (WT) ROP10 associates with the plasma membrane in an activation- and Cys199/205-dependent manner, with Cys160 further stabilizes membrane association. Unlike type-I ROPs, the constitutively active (CA) rop10CA mutant displayed reduced membrane affinity. Gas chromatography-mass spectrometry confirmed S-acylation of ROP10 by palmitic and stearic acids. Overexpression of WT ROP10 disrupted cell polarity, an effect abolished in the rop10 C160S mutant, establishing Cys160 as essential for polarity control. These results provide in vivo evidence for S-acylation of type-II ROPs and indicate divergence from type-I ROPs through partitioning into distinct plasma membrane subdomains.